An innovative and sustainable design of intangible Miao wax printing patterns in combination of diffusion model and fuzzy TOPSIS - Xinhui Kang; Wenjie You; Huaqian Xie (Humanities & Social Sciences Communications)
Abstract Miao wax printing is a dyeing and weaving process in which natural dyes replace chemical dyes. It is renowned for its unique patterns and exquisite craftsmanship. However, with the development of industrialization and the decreasing number of craftsmen, the skill of Miao wax printing is facing the risk of loss. Therefore, the diffusion model (DM) of artificial intelligence technology and the fuzzy comprehensive evaluation method are combined with each other to carry out innovative and sustainable design on patterns of traditional Miao wax printing, thus generating a new Miao wax printing pattern with both cultural inheritance and modern sense. Firstly, the pattern of Guizhou wax printing is taken as an example, semiotics is used to extract and establish a database composed of many wax printings of flower and plant patterns. Secondly, on the basis of learning large-scale Miao wax printing with flower and plant patterns, DM automatically generates 30 innovative patterns that have not been seen on the market. Then, based on customers’ preferences, fuzzy TOPSIS is used to evaluate and rank the esthetics of patterns; the top 20 patterns that is loved by customers are selected. The esthetic optimization design of wax printing pattern is carried out through the collaborative innovation of shape grammar and DM. Finally, by integrating the generated new wax printing patterns into the design of women’s fashion handbags, the profound Guizhou ethnic characteristics and personalized pursuit of customers are shown. Through the study and training of existing Miao wax printing patterns, a new pattern design is automatically generated. This not only improves the design efficiency, but also provides a rich source of inspiration for designers, thus promoting the in-depth integration of Intangible Cultural Heritage and modern industry, and bringing new opportunities for local economic development.